Indo‑Pakistani “hybrid war” for Kargil (Politeja, 2016)
The armed conflict in the Crimea and Eastern Ukraine introduced a new notion of hybrid war into security studies, but such kind of armed conflict is not anything new. History of wars provides at least a few examples when a country was attacked not by conventional armed forces, but by a mixture of special forces, information campaigns and backdoor proxies. Such armed struggles have taken place many times before, for example, during the so called Kargil War in 1999. Lessons for India emerged from the Pakistani operation in Kargil region necessitating a holistic national security review as well as rethinking of the nature of conflict and conduct in the new strategic environment and are very similar to the lessons learnt today by NATO, Poland and Baltic states concerning current warfare in Ukraine.